Logika Bahasa dalam Era Disinformasi: Analisis Kritik Terhadap Informasi Digital - Nanda Anisatus Sholihah; Nur Faizatul Ilmiah; M. Yunus Abu Bakar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
In the digital era, information can be accessed easily anytime and anywhere, so that people receive various news related to economic, political and individual issues. However, not all information circulating is valid. Some contain disinformation that is provocative, causing confusion, panic or distrust of certain institutions. This phenomenon shows the importance of language logic analysis in assessing digital information. Linguistic logic studies the structure, consistency, and meaning of messages, so it can identify logical ambiguities, oversimplifications, or the use of emotional language used to influence readers without a strong basis for argument. Through this approach, disinformation can be analyzed critically, not only from the facts, but also from the communication patterns that shape public perceptions. This research aims to evaluate how language logic is used in digital information, as well as how criticism of language structure can help assess the credibility of circulating content. Thus, understanding the logic of language not only functions as an academic tool, but also as an important strategy in digital literacy, which allows people to be more critical, selective and wise in receiving and disseminating information in the fast-paced information era.